2021
DOI: 10.3389/fonc.2021.650453
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix: Emerging Roles and Potential Therapeutic Targets for Breast Cancer

Abstract: Increasing evidence shows that the extracellular matrix (ECM) is an important regulator of breast cancer (BC). The ECM comprises of highly variable and dynamic components. Compared with normal breast tissue under homeostasis, the ECM undergoes many changes in composition and organization during BC progression. Induced ECM proteins, including fibrinogen, fibronectin, hyaluronic acid, and matricellular proteins, have been identified as important components of BC metastatic cells in recent years. These proteins p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 154 publications
(176 reference statements)
3
20
0
Order By: Relevance
“…Recent studies have shown that several COL and ITG genes are increased in a variety of tumors, and have been associated with unfavorable outcomes. Among these, COL1A2, COL3A1, COL5A2, ITGA5, ITGAV, and ITGB1 have been especially noted (48)(49)(50)(51)(52)(53). Therefore, for all these reasons, we realize that COL1A2, COL3A1, COL5A2, ITGA5, ITGAV, and ITGB1 genes expression provide important predictive information about metastatic-free and overall survival in PNENs and our results now confirm the predictive importance of COL and ITG genes in PNENs.…”
Section: Discussionsupporting
confidence: 77%
“…Recent studies have shown that several COL and ITG genes are increased in a variety of tumors, and have been associated with unfavorable outcomes. Among these, COL1A2, COL3A1, COL5A2, ITGA5, ITGAV, and ITGB1 have been especially noted (48)(49)(50)(51)(52)(53). Therefore, for all these reasons, we realize that COL1A2, COL3A1, COL5A2, ITGA5, ITGAV, and ITGB1 genes expression provide important predictive information about metastatic-free and overall survival in PNENs and our results now confirm the predictive importance of COL and ITG genes in PNENs.…”
Section: Discussionsupporting
confidence: 77%
“…For the CC, the DEGs of present study were particularly enriched in extracellular. Extracellular matrix, an important component of tumor microenvironment, is a complex network surrounding the cells [ 25 ]. Exosomes, released by multiple cells types, contain various types of protein, lipids, nucleic acids (DNA, mRNA, and miRNA) and other molecules [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no clear genetic abnormalities associated with the critical transition from DCIS to invasive cancer; however, there is emerging evidence linking this progression to tumor–induced changes in the microenvironment [ 3 ]. In particular, evidence supports a role for the immune/inflammation [ 102 , 103 , 104 ] and fibrogenic functions [ 12 , 105 , 106 ] of a wound–like host microenvironment in providing conditions to support early breast cancer cell spread and progression to a metastatic state. It is important to note that both host and tumor cells contribute to a cancer microenvironment, and that the evolution of a tumor–supporting microenvironment is chaotic in comparison to the defined stages of wound repair.…”
Section: Functions Of Hyaluronan: Size Matters In Cutaneous Repair and Breast Cancermentioning
confidence: 99%
“…Subsequent studies have identified the processes of inflammation and fibrosis, which are critical to efficient wound repair, as key microenvironmental factors that promote cancer progression [ 2 , 3 , 4 ]. Hyaluronan (HA) has emerged as an important extracellular matrix (ECM) regulator of inflammation and fibrosis in the setting of excisional wound repair [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ], and this polymer is also implicated in breast cancer progression [ 5 , 8 , 12 , 13 , 14 , 15 ]. Here, we review the well–regulated inflammatory and fibrogenic functions of HA polymers and two HA receptors—CD44 and RHAMM (HMMR)—in cutaneous wound repair and consider evidence that these functions also contribute to the progression of breast cancer.…”
Section: Introductionmentioning
confidence: 99%